Near-Infrared Light-Responsive Semiconductor Polymer Composite Hydrogels: Spatial/Temporal-Controlled Release via a Photothermal “Sponge” Effect - Wu, Yingjie (2017)
Near-infrared (NIR) light-responsive hydrogels are important for biomedical applications, such as remote-controlled release, but the NIR agents previously used were largely limited to heavy-metal inorganic materials such as gold nanoparticles. In this article, we report a new type of NIR photothermal-responsive hydrogel that can undergo structural changes in response to NIR light for biomedical applications in drug delivery and controlled release. The hydrogels synthesized by integrating a narrow-bandgap semiconductor polymer poly(diketopyrrolopyrrole-alt-3,4-ethylenedioxythiophene) with the polymerization of N-isopropylacrylamide show rapid and reversible mechanical shrinkage upon NIR light irradiation and can serve as carriers for anticancer drug loading and spatial/temporal control of drug release. These stimuli-responsive hydrogels, which can be prepared in different sizes and shapes, integrate photothermal properties and hydrogel characteristics and can provide on-demand, repeated, remote-controlled drug delivery for biomedical applications such as cancer treatment.